International aid in light of global poverty and inequality: Some unsubtle propositions - S. Subramanian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper re-asserts the importance of certain old-fashioned questions relating to international aid: what is the quantum of aid available in relation to the need for it? How may patterns of allocation, at both the dispensing and receiving ends of aid, be determined so as to take account of both poverty and inter-national inequality in the distribution of incomes? Can some simple and plausible rules of allocation be devised? If so, what correspondence does reality bear to these rules? The questions are addressed with the aid of some simple analytics relating to optimal budgetary intervention in the alleviation of poverty. The ideas discussed are clarified by means of data employed in elementary empirical illustrations.
Keywords: D63; F5; 330; international burden of poverty; lexicographic maximin solution; proportionality rule; Entwicklungshilfe; Armut